Kompetensi Sebagai Pemediasi Pengaruh Pelatihan dan Motivasi terhadap Produktivitas Pegawai - Kariza, Nadya; Maharani, Anita; Budiman, Rahmat (Jurnal Manajemen, 2022)
The goal of this research was to determine the influence of training and motivation on productivity, supposing that competence acts as a mediator. A variety of literatures are reviewed, including those on topics such as competence, training, motivation, and productivity, and a number of past studies are cited to demonstrate the relevance of connecting the aspects thought to effect employee productivity. This research employs a quantitative method with the Ministry of Education and Culture, subsequently referred to as Kemendikbud, in the general bureau and the purchase of goods and services as the subject of study. This study employs a structural model, which leads in a variety of research findings, including the following: training has been shown to impact competence, and competence has been shown to effect production. Then, using competence as a mediator of the influence of training on production, got findings.